The present situation of pesticide residues in China and their removal and transformation during food processing. (30th August 2021) - Li, Changjian; Zhu, Huimin; Li, Changyan; Qian, He; Yao, Weirong; Guo, Yahui
Highlights: The current situation of food safety in China was analyzed. Unstable pesticides can be transformed during food processing. Some pesticide metabolites are more toxic. Processing factor can improve food safety risk assessments. Abstract: Pesticide residues are one of the most important issues affecting food safety. In this review, the general situation of pesticide residues in fruits and vegetables based on the background of the Chinese fruit and vegetable industry is first described. On the basis of primary processing of agricultural products, the effects of processing methods on the removal and metabolism of pesticide residues are reviewed in this paper. In addition, the transformation mechanism of pesticides in crops and in the environment is discussed. Finally, this study summarizes the development trend of pesticide-residue monitoring methods. With the prohibition of a large number of pesticides in China, the risk of pesticide residues is gradually reduced. However, some highly toxic pesticides can still be detected. Furthermore, the development of high-resolution mass spectrometry screening methods and rapid and intelligent detection instruments is the development trend for pesticide monitoring in the future.